Analyzing environmental factors influencing the gestation length and birth weight of Hanwoo cattle - Jin, Shil; Kang, Sung-Sik; Won, Jeong Il; Kim, Hyoun Ju; Jang, Sun Sik; Kim, Sung Woo (Journal of animal reproduction & biotechnology (Online), 2024)
Background: This study focused on reproductive traits in Hanwoo cattle, specifically the environmental factors affecting gestation length and birth weight. Methods: The records of 1,540 cows calved at the Hanwoo Research Institute from 2015 to 2023 were examined. This study analyzed two populations, linebreeding Hanwoo (LBH) and general Hanwoo (GH), with all cows undergoing estrus synchronization and artificial insemination. The R software was used to compare the differences between the two populations and analyze the environmental factors affecting each trait. Results: The results showed that the average gestation length for LBH was 283.28 ± 5.93 days, which was significantly shorter than that of the GH, which had an average of 285.63 ± 6.21 days (p < 0.001). The average birth weight of LBH calves was 25.10 ± 3.69 kg, significantly lighter than GH calves, which weighed 27.26 ± 4.11 kg on average (p < 0.001). Analysis of environmental factors revealed significant differences in the gestation length of LBH based on dam parity, year, and season of calving. However, no significant differences were observed based on calf sex. For LBH, birth weight showed significant differences based on dam parity, year of calving, and sex of the calf, but not the season of calving. In GH, gestation length varied with dam parity and calving season, but not with calving year or calf sex. The GH birth weight showed differences based on dam parity, year of calving, and calf sex, but not the season of calving. Conclusions: Reproductive traits in the Hanwoo cattle industry are economically vital but are heavily influenced by environmental factors due to their low heritability. An accurate evaluation of the genetic potential of these traits requires an analysis of the environmental factors affecting them. The results of this study serve as foundational data for predicting the potential for genetic improvement in the gestation length and birth weight of Hanwoo cattle.